Studi Perkembangan Emosi Anak Melalui Pola Asuh Authoritative - Cahniyo Wijaya Kuswanto; Dona Dinda Pratiwi; Mas Hikmatun Nazila; Naura Nisrina Pelantino (Faculty of Teacher Training and Education, Musamus University, 2022)
The influence of child growth and development is one of the parenting patterns. Negative parenting patterns from parents will also have a negative impact on children's development. The purpose of this study was to determine the influence of authoritative parenting patterns on the emotional development of children aged 5–6 years. Authoritative parenting will give the child the opportunity to show that he is part of the people around him, thus having a significant influence on the child's emotional development. The research method is quantitative research with the type of research Ex-Post Facto. The population and sample of this study are 43 parents of RA Perwanida 2 Bandar Lampung students. The main data collection tool is questionnaires. Before use, the questionnaire instrument was tested to determine its validity and reliability. Then data analysis using a simple linear regression test. The results showed a simple linear regression value of the authoritative parenting pattern on children's emotional development of 11,100 with a sig value of 0.003 compared with the significance level of 0.05 (5 %). This sig value is less than 0.05 (5 %) means that there is an influence of authoritative parenting pattern variable (X) on the emotional development of children (Y) aged 5–6 years in RA Perwanida 2 Bandar Lampung with a coefficient test of determination where the magnitude is 34.6 % and as much as 65.4 % is influenced by other factors. This research hoped that parents are able to apply parenting patterns that can support the development and growth of the baby, especially the child's emotional development.